The Kya’s PTSD and Defense Mechanism as Represented in Delia Owens’ Where The Crawdads Sing - Marlinna, Dhui Ayu Tri; Ernawati, Asih (Smart Edu Center, 2024)
This descriptive qualitative study aims to identify the types of causes of post-traumatic stress disorder and to reveal how the defense mechanism experienced by Kya as the main character of the novel Where the Crawdads Sing. Sigmund Freud's psychological theory of defence mechanism is applied in this study. The data of this research are narratives, paragraphs, and dialogues of Delia Owen’s Where the Crawdads Sing that indicate the causes of post-traumatic stress disorder and the defense mechanisms used by Kya. The findings showed that Kya experienced post-traumatic stress disorder due to causes such as domestic violence, abandonment, bullying, isolation, rape, and murder. In addition, the defense mechanisms used by Kya in overcoming the causes of post-traumatic stress disorder and survival are employing denial to deal with the truth of the traumatic event she went through; sublimation to redirect her negative energy or focus on more productive and beneficial activities; and projection to project her own emotions onto other people, perceiving her own motivations or feelings in their actions. These defense mechanisms help Kya to adjust to difficult situations and find ways to survive due to the trauma she experienced.